The Close Interconnection between Mitochondrial Dynamics and Mitophagy in Cancer - Bordi, Matteo; Nazio, Francesca; Campello, Silvia (Frontiers in Oncology, 2017)
Recent decades have revealed the shape changes of mitochondria and their regulators to be main players in a plethora of physiological cell processes. Mitochondria are extremely dynamic organelles whose highly controlled morphological changes respond to specific and diverse pathophysiological needs. Thus, their qualitative control is crucial for the determination of cell function and fate. Moreover, ever-new metabolic changes, mainly attributable to mitochondrial (dys)functions, are strongly connected to cancer and its microenvironment. For this reason, the aspects controlling mitochondria activity and status are in the oncological spotlight. In this review, we elucidate the most intriguing discoveries related to two apparently independent but strictly interconnected processes crucial for the organelle functionality and fate, mitochondrial dynamics and mitophagy. We will mostly focus on their metabolic interconnections and regulations that can causally foster a tumoral context.